Evaluation of the moral school project obec case study of Wat Thung Noi school Kui buri district, Prachuap khiri khan province - kornkeaw, thippawan (Journal for Developing the Social and Community, 2023)
Evaluation of the Moral School Project OBEC : A Case Study of Wat Thung Noi School, Kuiburi District, Prachuap Khiri Khan Province The objectives of this time are 1) to assess the appropriateness of the context relevant to the project implementation 2) to assess the suitability of inputs used in the project implementation 3) to assess the suitability of the project implementation process 4) to assess the output of the project The sample group used in the assessment consisted of 8 teachers using the population as a sample group. The school committee consisted of 7 people from Purposive Sampling, 31 students in grades 4-6 from Purposive Sampling, using the Staffle B project assessment model. m (Stufflebeam) called the CIPP Model. Consisting of 4 issues of the Moral School Project Assessment Form, OBEC: Case Study of Wat Thung Noi School, Kuiburi District, Prachuap Khiri Khan Province, with a rating scale of 5 levels. The statistics used in the data analysis were percentage (%). Mean (Mean) and standard deviation (SD.) were analyzed for content and presented in a descriptive form. The evaluation results consisted of 3 phases as follows: Phase 1: Evaluate results before project implementation. 1.1 General information of the respondents found that most of the respondents were female, 45 people, the age of the respondents with the highest number ranged from 10-20 years, 31 people. The highest number was primary school students, 56 people. The status of the 77 respondents was found to be students and parents with the highest number of 31 people. 1.2 The results of the evaluation of the Moral School Project, OBEC: A case study of Wat Thung Noi School, Kuiburi District, Prachuap Khiri Khan Province, in context, it was found that the overall level was at a high level. The school environment was appropriate and conducive to project implementation, followed by project objectives consistent with school policy. and the principles and rationale of the project are consistent with the current reality, respectively, and the least mean item is the stakeholders involved in determining the project objectives and methods. 1.3 Evaluation results of the Moral School Project, OBEC: A Case Study of Wat Thung Noi School, Kuiburi District, Prachuap Khiri Khan Province on the import factor It was found that the overall level was at a high level. When considering each item, it was found that The point with the highest average value was that the personnel in the project implementation were appropriate, followed by the number of personnel in the project implementation was sufficient and the documents used in the project activities were appropriate and sufficient. The item with the lowest average is that the duration of the project implementation is appropriate Phase 2 Evaluation during project implementation 2.1 General information of the respondents found that most of the respondents were female, 45 people, the age of the respondents with the highest number ranged from 10 to 20 years, 31 people. The highest number was primary school, 56 people. The status of the 77 respondents was found to be students and parents with the highest number of 31 people. 2.2 Evaluation results of the Moral School Project, OBEC: a case study of Wat Thung Noi School, Kuiburi District, Prachuap Khiri Khan Province Operation process It was found that the overall level was at a high level. When considering each item, it was found that The item with the highest mean is Project activities help students achieve project objectives, followed by improvements in project implementation methods when they are found to be flawed. and has clearly and appropriately defined steps, details and methods of project implementation. and the item with the lowest mean is a form of organizing activities in the project that helps students to be enthusiastic about participating in the activities Phase 3 Evaluation at the end of the project 3.1 General information of the respondents, it was found that most of the respondents were female, 45 people, the age of the respondents with the highest number ranged from 10-20 years of 31 people. The highest number was primary school students, 56 people. The status of the 77 respondents was found to be students and parents with the highest number of 31 people. 3.2 Results of Assessment of Moral School Project, OBEC: Case Study of Wat Thung Noi School, Kuiburi District, Prachuap Khiri Khan Province, overall productivity was at the highest level. When considering each aspect, it was found that 1) School aspect The item with the highest average value was that schools built networks between schools and schools, schools built networks with religious organizations. and schools through the assessment of integrity and transparency in the operation of government agencies and the item with the least mean on the school side was that the school had information on morality 2) the management aspect Overall, it is at the highest level. when considering each item It was found that the items with the highest average value were the executives having a style/innovation in moral management, followed by the managers having the knowledge and understanding of supervision. Follow up on school project implementation and the item with the lowest mean For the administrators, there are manuals/guidelines/documents of the Moral School OBEC. 3) Teacher aspect, in general, it was at a high level. When considering each item, it was found that The item with the highest average value was that teachers had to build a network within the school, followed by measuring and evaluating morality and using the assessment results to improve students' development. and the item with the lowest average. On the teacher side, it was the teacher having the results and bringing the results of learning exchange activities at the educational service area/provincial office level. 4) The students, overall, was at a high level. When considering item-by-item, it was found that the item with the highest average value was that the students had a moral project based on their moral identity. Or the concept of moral school OBEC, there is a summary of knowledge from the moral project. And the moral project can be a model for other schools. and the item with the least average value, on the student side, was a good leader and follower in organizing activities according to moral identity or the moral school concept framework OBEC; desirable characteristics according to the moral school concept framework OBEC and morality and identity of the school. As for students, it was found that the overall level was at a high level. When considering each item, it was found that The highest average value was the participation in moral and ethical activities regularly organized by the school, followed by the students being able to work with others. happily resolve conflict with peace and reconciliation And the item with the least average on the student side was to complete the assigned tasks.